Coral Rock Thickness Grounding System Switchyard Substation In Clay - Janardana, IGN; Wijaya, I Wayan Arta (Journal of Electrical, Electronics and Informatics, 2023)
The grounding of the equipment at the substation switchyard location is given a layer of coral about 10 cm above the ground surface to reduce the tension difference on the ground surface and increase the resistance of the human feet around it. The purpose of this study was to determine the thickness of the coral in the grounding system of switchyard equipment in clay. This research analysis method calculates the results of the coral thickness value to achieve the step voltage and touch voltage values ??according to the IEEE Std 80-2013 standard so that it can provide safety for the equipment and people around it. The results of this study are that the thickness of the coral 0.15 meters produces a touch voltage value = 150.3675 volts (dry conditions) and 148.63 volts (wet conditions) and the step voltage is the smallest and best with a value = 206.83 volts ( dry conditions) and 163.98 volts (wet conditions when compared to the thickness of the coral 0.08 meters to 0.14 meters, so it is concluded that the thickness of the coral is best to be installed at the substation on clay of 0.15 meters is good when the soil and coral are wet or dry, so that it has an impact on the function of the grounding system to function properly and safely for equipment and humans.   Keywords— Coral, Earthing, Clay.